Comparison of Analgesia in Subtenon and Peribulbar Anesthesia - Abdul Rauf, Ayyaz Hussain Awan (Pakistan Journal of Ophthalmology, 2007)
Purpose: To compare degree of analgesia in subtenon and Peribulbar local anesthesia in patients undergoing extra capsular cataract surgery. Material and Methods: Quasi-experimental interventional study carried out in Department of Ophthalmology, PNS Shifa, Karachi extending from October 2004 to March 2005. 100 patients undergoing extra capsular cataract extraction were randomly divided into two groups comprising 50 patients each. Group I was given subtenon and group II peribulbar local anesthesia respectively. Patients were asked about pain scoring during surgery and degree of analgesia was marked on a specified performa. Results: Analgesia was effective and immediate with minimal volume of anesthetic agent and procedure was less painful in subtenon local anesthesia as compared to peribulbar local anesthesia. There is no need for globe compression and preoperative sedation. The use of topical anesthesia prior to subtenon local anesthesia makes this technique almost pain free. Incidence of top up anesthesia is less in subtenon anesthesia then in peribulbar anesthesia. Conclusion: The subtenon anesthesia is more effective with fewer complications as compared to peribulbar anesthesia due to the cannula used being blunt and the infiltration being superficial as compared to peribulbar route.